Stimulasi Kemampuan Siswa dalam Mengarang melalui Mind Mapping - Fatimah Zuhra; Zulfitri Zulfitri; Siti Habsari Pratiwi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
Writing stories requires writing competencies that have existed and started since elementary school / MI, because by writing, students can express their feelings, ideas, and ideas to others. This type of research is Classroom Action Research. The data collection technique used is a test. The results of the study revealed that theuse of the mind mapping method in writing student narrative essays is more active, easy to understand learning materials and easier to express ideas and thoughts in writing form, namely narrative essays. Increased use of mind mapping methods in writing narrative essays. Based on the first cycle data with a complete score of 18 students and the incomplete 15 students, with a percentage of 55%. While the average value amounts to 70. In cycle II, the incomplete grades were 3 students and the completed 30 students, with a percentage of 91% where an increase occurred